PENENTUAN RUTE TERPENDEK MENUJU PUSAT PERBELANJAAN DI JAKARTA MENGGUNAKAN ALGORITMA DIJKSTRA - Jodi Setiawan; Rezy S. Prakoso; Kristien Margi Suryaningrum (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
Abstract : Shopping centers are easy to find in big cities like Jakarta and because there are too many times people are often confused which one to go to, not to mention if people from outside Jakarta come and want to visit a shopping center. The problem to choose a shopping center that encourages researchers to conduct a study to develop applications to find the nearest shopping center using the Dijkstra algorithm that can be used on smartphones in order to make it easier to find and find shopping centers around users. The application was designed using flowchart and UML and was made using Android Studio with the help of the Google Maps API to display maps, display pins, find and display the nearest route using latitude and longitude from Google Maps. Algorithm to calculate and determine the route that must be traversed using the Dijkstra algorithm. The accuracy of the calculation results using the Dijkstra algorithm reaches 93%